Closed-Small Submodules and Closed-hollow Modules. - Esraa Hashim (Wasit Journal for Pure Sciences, 2023)
The aim of this study is to present the concept of closed-small submodule and closed-hollow module as generalization of small and hollow concepts respectively. As evidence, attributes of these ideas. Moreover, we study the concept of the closed-Radical of   as a generalization of Radical module .